Pochodzenie nowobabilońskich dokumentów prawnych z Kolekcji Ashmolean Muzeum - Chmielowski, Stanisław (Folia Praehistorica Posnaniensia, 2019)
The majority of currently known Neo-Babylonian legal and administrative documents from Kish come from excavations held on this site by the joint expedition of Oxford – Field Museum (Chicago) between 1923–1933. They are now housed in the Ashmolean Museum, Oxford. However, ca. 40 Neo-Babylonian ‘Kish’ tablets, i.e., written in Ḫursagkalamma or Kiš, are present in other collections. How did they end up in these museums assuming that most of them was acquired in the last quarter of the 19th century, 30–50 years before the expedition mentioned above? I suppose that they were not found in Kish, even though their Ausstellungsort indicates quite the opposite. They instead come from nearby Babylon or Borsippa cities. The analysis conducted in the article seems to confirm this assumption, and for most cases, the provided attribution should be considered. Additionally, tablets under discussion are testimonies of the vivid economic life of entrepreneurial Babylonians in the first millennium BC.